Effects of flow training on movement, survival, and habitat associations of age-1 Colorado pikeminnow stocked in the San Juan River, Utah, and New Mexico - Cleveland, John E. (Kansas State University, 2024)
Stocking of hatchery-reared fish is an increasingly important management action to conserve and restore native fish populations. Colorado pikeminnow (Ptychocheilus lucius) was historically abundant throughout the Colorado River basin until the construction of dams and introduction of nonnative species caused a rapid decline and federal listing as endangered in 1973. Following the presumed extirpation of pikeminnow in the San Juan River in the late 1990s, a stocking program was developed in 2003. Due to an increasing adult abundance and potential for spawning, stocking protocols were changed from stocking young of year to age-1 pikeminnow with passive integrated transponders (PIT) tags to distinguish wild spawned and hatchery reared individuals. The addition of unique tags also allowed for hatchery experimentation such as flow training which was implemented in 2022 and 2023 to increase the survival of stocked age-1 pikeminnow. I used radio telemetry to compare movement, survival, and habitat associations among flow-trained and different size classes of non-flow-trained pikeminnow. We also used PIT tags implanted in stocked pikeminnow to evaluate differences in detection rates across treatments. The mean rate of movement for radio-tagged pikeminnow was similar across treatments (-0.08 ± 0.48 km/hr). At the conclusion of 60 days, no control (0%), one flow-trained (3.3%) and 12 larger pikeminnow (34.3%) were detected and determined to be alive and within our study reach across both years. One individual from the radio-tagged flow-trained group was detected 255 river kilometers downstream approximately five days post stocking in 2022 (rate of -2.13 km/hr), demonstrating the ability to move long distances following stocking. Effects of terrestrial predation was observed in both years with 11 radio transmitters and 59 PIT tags found on dry land within the river corridor. Another radio transmitter was triangulated in a great blue heron (Ardea herodias). Overall, results suggest stocked pikeminnow dispersed quickly downstream; flow-trained pikeminnow prior to stocking did not increase retention of radio tagged individuals; and terrestrial predators may be a large source of mortality. Increasing the duration or velocities of flow training, prey training, or using alternative stocking sites may reduce losses due to predators and emigration.
Keywords: Movement; Telemetry; Colorado pikeminnow; Stocking; Hatchery enrichment